High seroprevalence of SARS-CoV-2 in elderly care employees in Sweden - Lindahl, Johanna F.; Hoffman, T.; Esmaeilzadeh, M.; Olsen, B.; Winter, R.; Amer, S.; Molnár, C.; Svalberg, A.; Lundkvist, Å. (Informa UK Limited, 2020)
The COVID-19 pandemic is growing and spread in the Swedish elderly care system during April 2020. The increasing number of employees on sick-leave due to COVID-19 creates severe logistic problems. Some elderly care homes therefore started to screen their personnel to secure the safety of the elderly and to avoid unnecessary quarantine of potentially immune employees. Secondary data from a screening with a COVID-19 rapid test for detection of SARS-CoV-2-specific IgM and IgG of 1,500 employees in 22 elderly care homes in Stockholm, Sweden, were analyzed. Seropositive employees were found in 21 out of the 22 care homes. In total, 23% (231/1,005) of the employees tested positive for antibodies against SARS-CoV-2, and 14.3% (144/1,005) were found positive for IgM (either alone or combined with IgG), indicating recent or present infection. Of those that tested seropositive, 46.5% did not report any clinical symptoms, indicating pre- or asymptomatic infections. Reported symptoms with the highest correlation with seropositivity were fever and loss of smell and taste. These results suggest that antibody testing of employees in elderly care homes is valuable for surveillance of disease development and a crucial screening tool in the effort to decrease the death toll in this pandemic.